BLOOD GROUP AND ITS RELATIONSHIP WITH DIABETIC - Hashim, Aswan Mahmood; Manje, Nawras Bahaa (Journal of Medical Genetics and Clinical Biology, 2025)
Objective: Diabetes is described in this article as a metabolic disease that results in hyperglycemia, or elevated blood sugar. DM pathophysiology may be divided into two primary groups. type 1 and type 2 Its connection to blood types is examined. The four basic "ABO" phenotypes—"A," "B," "O," and "AB"—make up the "ABO" system. ABO phenotypic blood types are polymorphic, genetic, antigenic substances found on the surface of red blood cells as well as other organ cells. Method: From people of both sexes (male and female), with ages ranging from 7 to 80, 97 samples were taken. People with diabetes may be anywhere from 7 to 80 years old, based on blood sugar levels. Results: In contrast to type 2 diabetes, which is more common in those over 40, type 1 diabetes may develop at any age. O+ diabetes is the most common form, and men are more likely than women to get it. The highest blood sugar level for a person aged 30 was 600. The lowest percentage is 91 for a person who is 27 years old. O+ was shown to be the kind most affected by diabetes. Blood group AB is the one least affected by diabetes. Novelty: If genes "A" and "B" are present or absent, the individual's blood class is determined by small carbohydrate epitopes. Scattered over 18 kb, the gene's seven exons are referred to as "ABO" blood types. It is located on chromosome 9q34.